Hate speech in the Undercover.Id Comment Column for Pragmatic Studies: Ujaran Kebencian pada Kolom Komentar Undercover.Id Kajian Pragmatik - Ahsanur Rijal; Ahmad Ahmad (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2024)
This research is a qualitative descriptive study. The objectives of this study are: 1) To describe the form of hate speech in the Undercover.Id comment column, 2) To describe the form of hate speech in the Undercover.Id comment column. The primary data source in this study is language in social media which contains elements of hatred, including Instagram accounts that focus on utterances in the undercover.id comment column which will be held from Mei to Juli 2024. Secondary data in book, journal, that is relevance by research and can strengthen data. It is a technique an instrument in research done preach turnaround method, read, and note. Whole the data analyzed through four stages: (1) description, (2) classifications, (3) interpretation, (4) and eksplanasi. Analysis, speech form hatred in columns comments undercover.id, the sacrilege, defamation, sacrilege, unpleasant, what provoke or incites, and spreading falsehood. Based on form kebahasaan, a unit of grammatical mengindikasikan speech hatred in a text may include sentence declarative consisting of declarative active and passive, a sentence the imperative consisting of the imperative ordinary, the imperative the provision of licenses, the imperative ban, and interrogative. Keywords speech: hatred, undercover.id, pragmatic